Quantum computing with mixed states - Siomau, Michael; Fritzsche, Stephan (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2011)
We discuss a model for quantum computing with initially mixed states. Although such acomputer is known to be less powerful than a quantum computer operating with pure(entangled) states, it may efficiently solve some problems for which no efficientclassical algorithms are known. We suggest a new implementation of quantum computationwith initially mixed states in which an algorithm realization is achieved by means ofoptimal basis independent transformations of qubits.
Gesehen am 17.10.2022